Analisis Pengaruh Situasi Kerja, Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja - ., Syahyono (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2016)
The background of this research is to collect data and information on employee perceptions of workplace situations , job satisfaction and motivation are running at this time and its relationship with the employee's performance . The purpose of this study presented is to know Influence Analysis : work situation , work job satisfaction , motivation and employee performance environment Pt . Rays Griya Utama . This research was conducted in Pt . Rays Griya Utama . Data were collected by using a questionnaire , and sampling this study as many as 65 employees of probability sampling . The data analysis method used is multiple regression test , F test , and the coefficient of determination (R Â²) The results showed that: 1). Partially Employment Situation t test variable (X1) effect on the performance of employees at PT. Rays Griya Utama. It is known from p-value less than 0.05. 2). Partially Job Satisfaction variable t test (X2) effect on the performance of employees at PT. Rays Griya Utama. It is known from p-value less than 0.05. 3). Partially Work motivation variable t test (X3) does not affect the performance of employees at PT. Rays Griya Utama. It is known from p-value greater than 0.05. Based on the result showed that motivation in PT. Rays Top Griya need not be held because the employees are self-motivated, and to increase the motivation of employees need their money incentives for high achievers. 4). Simultaneously (F test) Situation variable Work, Job Satisfaction, and Work Motivation has a significant influence on employee performance in PT. Rays Griya Utama. It is known from p-value less than 0.05